PREPARASI NANOPARTIKEL OKSIDA BESI BERBASIS PASIR ALAM LOGAS DIDOPING KOBALT SEBAGAI MATERIAL LINGKUNGAN - Erwin Amiruddin; Amir Awaluddin; Muhammad Rizki (Universitas Riau, 2023)
The cobalt doped iron oxide nanoparticles have been prepared by ball milling method using Logas natural sand as a raw material. The milled iron oxide nanoparticles were doped using cobalt with concentration of 0, 5, 10, 15, and 20 wt.%. The structural, magnetic and optical properties were studied using X-ray diffractometer (XRD), vibration sample magnetometer (VSM), and UV-Vis spectroscopy, respectively. The samples show cobalt-hematite nanoparticles as indicated through XRD measurement. The XRD measurements confirmed the formation of crystalline, rhombohedral crystal structure and hematite nanoparticles. The average crystallite size calculated using Scherrer formula found to be 38.51, 35.67, 33.75, 32.73, and 31.53 nm after being doped with cobalt 0, 5, 10, 15, and 20 wt. %, respectively. The samples exhibited weak ferromagnetic behaviour with the coercivity ranged from 124 Oe to 299 Oe. The optical properties strongly depend on cobalt content and showed that the band gaps of cobalt doped hematite decrease with increasing cobalt content. This work suggests that the prepared iron oxide nanoparticles are attractive photo Fenton catalysts for the degradation of methylene blue in the water.